2017
DOI: 10.3892/etm.2017.4166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ankaferd BloodStopper on bone healing in an ovariectomized osteoporotic rat model

Abstract: Bone defects resulting from oncological surgical resections, congenital facial anomalies, trauma or infection represent a significant and common clinical problem. The present study aimed to evaluate the effects of a commercially-available medicinal plant extract product, Ankaferd BloodStopper (ABS), on bone healing. The present study was performed on 24 female ovariectomized (OVX) rats. A defect on each rat calvarium was created using a trephine burr prior to the rats being divided into two groups. Defects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…( 2016) reported that ABS increased clinical attachment gain during the treatment of intrabone periodontal defects. In addition, other studies indicating that ABS has positive effects on bone formation and wound healing were consistent with our results (Ezirganli et al., 2017; Tanik et al., 2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…( 2016) reported that ABS increased clinical attachment gain during the treatment of intrabone periodontal defects. In addition, other studies indicating that ABS has positive effects on bone formation and wound healing were consistent with our results (Ezirganli et al., 2017; Tanik et al., 2018).…”
Section: Discussionsupporting
confidence: 94%
“…In addition to studies evaluating the hemostatic effects of ABS, there have been many studies regarding its role in bone healing (Cakir et al., 2015; Ezirganli et al., 2017; İşler et al., 2010; Pamuk et al., 2016; Şimşek et al., 2013; Tanik et al., 2018). However, this is the first study of its effects on periodontal fenestration defects and its potential utility as an alternative agent promoting periodontal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…1 The OVX rat model has been validated as a clinically relevant model of human postmenopausal bone loss and is commonly used to investigate the pathophysiology, diagnosis, and therapy of osteoporosis. 42 As shown in Figure 4, micro-CT scanning showed that the BV was significantly reduced after ovariectomy, while ARS staining revealed decrease in the osteogenic ability of BMSCs from OVX. Our previous studies have shown that P28 successfully stimulated osteogenic differentiation of BMSCs from healthy tissues in vitro and enhanced bone regeneration in normal animals in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…The high endemic locations accounting for almost 50% of HBV-related cases belong to the African subcontinent, Asian subcontinent, the Great Amazon region, and part of Middle Eastern nations wherein the HBsAg rate is recorded to be at a whopping ≥ 8%. The low endemic rate locations, accounting for 10–12% of HBV-related cases, belong to the European subcontinent, the United States, and Australia, wherein the HBsAg rate is recorded as low as < 1%. , Furthermore, this causes hepatocytes to become cancerous over time. Several variables have been implicated in the etiology of HBV-associated HCC, including integrating HBV genes into host cells, causing genomic instability due to mutation and activating signaling pathways promoting malignancy.…”
Section: Viruses Associated With Oncogenesismentioning
confidence: 99%